7th International Immunoglobulin Conference: Neurology. (December 2014) - Nobile‐Orazio, E.; Lewis, R. A.
Summary: Immunoglobulin (Ig) therapy has been used and studied as a treatment for a variety of neurological conditions for decades. In some of these disorders Ig therapy has a significant role as a first‐line treatment. This session explores the use of Ig therapy in immune‐mediated peripheral neuropathies and various central nervous system (CNS) diseases. Informative practice points relating to the management and treatment of these diseases are discussed. Potential future neurological indications for Ig therapy, as well as data on efficacy and possible mechanisms of action, are also presented. In peripheral immune‐mediated neuropathies, data show good response rates to Ig therapy and it is often used as a first‐line treatment. Intravenous immunoglobulin (IVIg) and subcutaneous immunoglobulin (SCIg) are both well tolerated, but dose and dosing frequency should be based on individual clinical responses. In Alzheimer's disease, although clinical data show no significant differences between IVIg and placebo, biomarker studies indicate that plasma‐derived antibodies may be involved in clearance of amyloid aggregates from the brain. Data suggest that the use of high IVIg doses in early‐stage Alzheimer's treatment may warrant further investigation. Ig therapy is considered a valuable option for autoimmune encephalitis, an antibody‐mediated CNS disease. Combination treatment with IVIg and corticosteroids shows promising results and is proposed as a first‐line treatment in these disorders. Until recently, very little was understood about the pathogenesis of chronic pain disorders. Data now indicate that perpetuation of the pain response may be underpinned by central immune activation. Some data suggest that Ig therapy may mitigate this effect, with good response rates in a number of studies, but these data need confirmation.